Ozone therapy as a treatment option against COVID-19: a literature review (Research, Society and Development, 2021)
Ozone therapy is a treatment that uses ozonized medicinal gas, with a mixture of ozone and pure oxygen in concentrations of 5% and 95% respectively. This therapy has considerable and expressive benefits when administered in adequate doses, as it has a strong antioxidant, bactericidal, fungicidal and antiviral action. Among the antiviral actions, ozone therapy has interesting characteristics to fight the coronavirus. In this sense, this research intends to carry out a literature review on the application of ozone therapy in the treatment of COVID-19 infection. This study is an integrative bibliographic review of the exploratory type of qualitative character, with data collected in articles, monographs and Brazilian legislation from March 2011 to March 2021. Through the results, it was possible to see that ozone therapy can be used as monotherapy or adjuvant in association with other drugs in the treatment against COVID-19, since after the use of this therapy there was an improvement in the clinical picture, in the biochemical markers of inflammation and radiological without presenting side effects, becoming effective and beneficial treatment for patients. This work corroborates the expansion of the understanding and spread of ozone therapy and reports the social and scientific relevance of the use of ozone therapy in the treatment of COVID-19.